Designing of Retaining Structures of Reinforced Soil with Limit Conditions Method - Edward Hutnik; Andrzej Surowiecki (Communications - Scientific letters of the University of Zilina, 2004)
The principles of limit conditions method in designing modern retaining structures of reinforced soil are presented. The principles are elaborated according to French Standard NF P 94-200 [1, 3]. Procedures of checking of particular kinds of stability are described. The most frequently adopted combinations of loads are given together with partial factors of safety of external, internal and general stability, method factors, friction factors of soil medium-reinforcement and values of partial safety factors of settlement.